Strategi Belajar Siswa Kelas XII di MAN 3 Kediri dalam Menghadapi Tes Kemampuan Akademik (TKA) Bahasa Indonesia - Mayada, Mayada; Hardinanto, Eko; Faizi, Ahmad (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
This study aims to analysis (1) learning strategies that student use in facing the Indonesian Academic Competency Test (TKA) at MAN 3 Kediri, (2) learning model that teachers apply in facing the Indonesian language Academic Competency Test (TKA) at MAN 3 Kediri, (3) things that support students learning process in facing the Indonesian language Academic Competency Test (TKA) at MAN 3 Kediri. This resulting data source was obtained from a questionnaire distributed by researches to class XII students at MAN 3 Kediri. The data collection technique used was a student questionnaire or survey via a google form plate which was filled in by class XII students at MAN 3 Kediri. The data analysis technique used is qualitative descriptive analysis to explain the results of the survey obtained. The data validity technique employed is triangulation. The analysis results show that students receive learning strategies through direct instruction or by practicing the material directly through exercise questions. Additionally, the difficulty level of the questions varies, ranging from lower-level to higher-order thinking skills (HOTS). Furthermore, the teacher also prepares an appropriate teaching model to help students face the Indonesian Language TKA (National Competency Test). The result shows that the teacher applies the PAIKEM approach (active, innovative, creative, effective, and enjoyable). The supporting strategy includes practice questions that encourage students' understanding.